MENINGKATKAN KEMAMPUAN BAHASA ANAK USIA DINI MELALUI KEGIATAN PENYEDIAAN BUKU BERGAMBAR : IMPROVING EARLY CHILDREN'S LANGUAGE ABILITY FROM PICTURE BOOK PROVISION ACTIVITIES - MUTIA MUHALISIAH; ASTUTI DARMAYANTI (incrementapedia, 2023)
At a young age, children begin to grow and develop rapidly. Educators, parents, caregivers, or other adults around children need to set up a stimulating role by providing a conducive environment for children to reach their full potential. Questions were asked about social, emotional, and independent life, ethical and religious principles, language skills, cognitive, physical/motor, and artistic potential. Language is a tool of communication with other people. The teacher-child approach, which is the subject of this qualitative research, is the method adopted in this study. A method known as "purposeful sampling" uses specific objectives to select respondents and select sources or objects of research based on various factors. Triangulation, interviews, and observation of the following data collection methods. The use of primary data sources and techniques as well as participant observation are used in qualitative research. Based on the findings of this study, it can be concluded that giving picture books can improve language skills in early childhood at RA AL-HIDAYAH groups A and B. This can be done by observing how the teaching staff at RA AL-HIDAYAH Institute are very enthusiastic and work hard to continue to improve children's language skills. By using the media of picture books, children's language development is also carried out personally.